2017
DOI: 10.1002/lary.26562
|View full text |Cite
|
Sign up to set email alerts
|

Steroid intracochlear distribution differs by administration method: Systemic versus intratympanic injection

Abstract: NA. Laryngoscope, 128:189-194, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…In contrast, intratympanic steroid injection requires low concentrations of steroids, as the steroid is directly delivered through the round window [9]. Lee, et al [10] compared the steroid concentrations in the perilymph when dexamethasone was injected to mice through the round window or through the abdominal cavity and reported that injection through the round window results in higher steroid concentrations and maintains the concentration for a longer period of time. Therefore, despite intratympanic steroid injection being widely used in the clinical treatment of sudden sensorineural hearing loss, various opinions on the optimal dose, medication, and administration methods are still being proposed.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, intratympanic steroid injection requires low concentrations of steroids, as the steroid is directly delivered through the round window [9]. Lee, et al [10] compared the steroid concentrations in the perilymph when dexamethasone was injected to mice through the round window or through the abdominal cavity and reported that injection through the round window results in higher steroid concentrations and maintains the concentration for a longer period of time. Therefore, despite intratympanic steroid injection being widely used in the clinical treatment of sudden sensorineural hearing loss, various opinions on the optimal dose, medication, and administration methods are still being proposed.…”
Section: Discussionmentioning
confidence: 99%
“…In general, local administration of MP or dexamethasone leads to greater perilymph concentration than systemic application (Bird et al, 2007; Yang et al, 2008; Grewal et al, 2013; Creber et al, 2018; Lee et al, 2018). For example, in humans, local IT administration of 40 mg of MP led to a 126-fold greater perilymph concentration after a single 1 mg/kg IV injection and 33-fold increase after 10 mg/kg IV infusion (Bird et al, 2007).…”
Section: Local Delivery Of Oto-protective Compounds To the Cochleamentioning
confidence: 99%
“…Additionally, higher and more prolonged intracochlear uptake was seen after administration of 3 IT injections of 20 μL of 10 mg/mL of fluorescein isothiocyanate-labeled dexamethasone in comparison to 3 i.p. injections of 60 μG/100 g (Lee et al, 2018). Tissue labeling after local administration mirrors glucocorticoid receptor distribution with the highest labeling in the SGNs, organ of Corti, and lateral walls (Lee et al, 2018) corresponding to the highest concentration of receptors in cochlear structures (Zuo et al, 1995).…”
Section: Local Delivery Of Oto-protective Compounds To the Cochleamentioning
confidence: 99%
See 2 more Smart Citations